Characterization of Ovarian Tumors and Staging Ovarian Cancer With 3-Dimensional Power Doppler Angiography: Correlation With Pathologic Findings. Issue 3 (1st March 2013) - Kalmantis, Konstantinos; Rodolakis, Alexandros; Daskalakis, George; Antsaklis, Aris
Abstract : Objective: The aims of this study were to evaluate ovarian tumors with 3-dimensional power Doppler angiography (3-DPDA), to determine its correlation with histology findings, and to explore its role in staging patients with ovarian cancer. Methods: Three hundred eighteen women with an unknown unilateral pelvic mass were referred for preoperative evaluation by 3-DPDA angiography. Patients' ages ranged from 18 to 72 years (47.4 ± 13.8 years). Sonographic criteria used for the characterization of ovarian tumors were based on a system that included morphological characteristics, histological evaluation, and Power Doppler imaging. Results: Two hundred twenty-five tumors were histopathologically diagnosed as benign and 93 as malignant. Sensitivity and specificity of the 3-DPDA of ovarian masses reached 93.5% and 92.9%, respectively, whereas positive predictive value was 84.5% and negative predictive value was 97.2%. Conclusions: Three-dimensional power Doppler sonography is an effective imaging technique for discriminating ovarian neoplasms and classifying them according to histopathology.